Phenotypic Characteristics of Watish Sheep - Ishag, Ibrahim A.; Osman, Sana E.; Idris, Ahmed O. (جامعة سنار, 2013)
الهدف الرئيس من هذه الدراسة هو توصيف أغنام الوتيش التي تربى جنوب ولاية سنار وفقاً لمميزاتها المظهرية. وتم الحصول على بيانات عن قياسات الجسم لعدد 180 حيواناً بصورة عشوائية من قطعان مختلفة من ثلاث مناطق بولاية سنار هي أبو نعامة ، ود النيل واللكندي. وصنفت البيانات حسب المنطقة وعمر الحيوان. أظهرت النتائج أن متوسطات وزن الجسم، طول الجسم ، الارتفاع عند الغارب ومحيطي الصدر والبطن كانت 37.8 ± 12.9 كجم و 68.9 ± 11.1 سم و 59.8 ± 10.8 سم و 78.2 ± 12.7 سم و 89.1 ± 19.3 سم على التوالي. ودلت نتائج تحليل التباين أن لعمر الحيوان تأثير معنوي (احتمالية < 0.001) على جميع قياسات الجسم التي شملتها الدراسة. بينما كان للمنطقة تأثير معنوي (احتمالية < 0.001) على كل الصفات المدروسة ما عدا طول محيط الصدر وطول الرقبة. ثمة حاجة إلى المزيد من البحوث والدراسات بشأن أغنام الوتيش خاصة في مجال إنتاج اللحوم وتحليل النظام الإنتاجي، لاستخدام نتائج هذه الدراسات في التحسين الوراثي The main objective of this study was to characterize “Watish” sheep which was bred in south Sinnar State, Sudan according to their phenotypic feature. Body measurements data were obtained on 180 unrelated animals of “Watish” sheep from three regions vis Wad Elnayal, Ellakandi and Abu-Naama. The data were classified according to region and age of animal. The results showed that the averages of body weight, body length, wither height, chest girth and abdominal girth were 37.8±12.9 kg, 67.8±11.1 cm, 59.8±10.8 cm, 78.2±12.7 cm and 89.1±19.3 cm respectively. The analysis of variance results showed that the age of animal had significant (P<0.001) influence on the all studied body measurements. Also the region had significantly (P<0.001) affected all studied traits except chest girth and neck length. Further studies on Watish sheep are required in field of meat production and analysis of production system and use these information to improve genetic potential of this subtype.
Keywords: أغنام الوتيش -- إنتاج اللحوم -- ولاية سنار، السودان